Speed Regulation of Direct Current Motor Using AC-DC Buck Boost Converter by using Soft Starter Method - Khanh, Nguyen Truong; Minh, Hoang Anh; Dung, Doan Pham; Paarbrahm, Vaamdev; Roux, John Charters (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2024)
Regulating the speed of direct current motors is essential in a variety of industries. The speed of direct current can be controlled by adjusting armature resistance, voltage and field current. Voltage regulation can be achieved by utilizing an AC-DC buck-boost converter for increasing and decreasing voltage. Additionally, it is important to take into account the initiation of a DC motor. Initiating operation of a DC motor necessitates a significant current to prevent potential harm to the insulation. Due to this, it is important to keep the current low when starting a DC motor. One method to decrease the initial current is by using a soft starter, where the reference current is compared to the motor's armature current. This research resulted in the development of a circuit that efficiently adjusts voltage levels with a pulse generator, making it easy to regulate the speed of direct current motors. A PI controller can also regulate the velocity of a direct current motor. During the trial, it was discovered that the initial current in a direct current motor never went beyond 25.6 amperes, making this technique highly efficient for initiating a direct current motor.